Design electrical model noise and perform nonlinearities of SiGe bipolar phototransistor - Diop, Ahmadou Moustapha; Polleux, Jean-Luc; Algani, Catherine; Mazer, Said; Fattah, Mohammed; Bekkali, Moulhime EL (International Journal of Innovative Research and Scientific Studies, 2023)
This study uses a new model developed in this paper to investigate the performance of a heterojunction phototransistor (HPT) on SiGe technology. An electrical model of an optical window phototransistor was developed based on the Ebers & Moll model, and its performance was evaluated by examining the error vector magnitude (EVM) when integrated into a mobile communication setup. Simulations showed that the HPT exhibited an EVM lower than 8%, enabling 64-Quadrature Amplitude Modulation (64-QAM) modulation for the mobile network. The third-order intercept point (IP3) measured 22 dBm, making the HPT suitable for Radio over Fiber (RoF) links in the detection block. The noise model of the HPT was also studied, resulting in a favorable power spectral density (PSD) that facilitates accurate modeling and prediction of the noise behavior of HPTs across various applications. This study provides valuable insights into the performance of HPTs on SiGe technology, enabling the development of more precise and efficient models for future research and practical applications. The results carry significant implications for the use of HPTs in optical communication systems.